Partikel pun dalam Novel Rentang Kisah Karya Gita Savitri Devi: Kajian Aspek Gramatikal dan Semantis - Naili Nurjanah; Burhan Eko Purwanto; Afsun Aulia Nirmala (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2021)
This research examines the grammatical and semantic aspects of particles in the novel of Rentang Kisah by Gita Savitri Devi. The purpose of this research is to describe the grammatical and semantic aspects of the particles pun in the novel Rentang Kisah by Gita Savitri Devi. The approach in this research uses a qualitative approach. The researchers obtained 30 sentences that contain particles pun in the novel Rentang Kisah by Gita Savitri Devi. The research result, namely: grammatical aspects of 19 findings include, (1) conjunction 15 data (50%), and (2) parallelism 4 data (13.33%). Semantic aspects as many as 11 findings include, (1) the relationship between the additive in terms of time 4 data (13.33%), (2) the additive relationship that is not related to time 2 data (6.67%), and (3) the contention relationship 5 data (16.67%).